Investigating the link between vitamin d deficiency and depression and anxiety in medical students at Jazan university: a cross-sectional study - Oraibi, Omar; Somaili, Mohammed; Jaawna, Essa; Alfaraj, Sarah; Majhali, Jalal; Zuqayl, Alhanouf; Hadadi, Abdulrahman; Ageeli, Ruba; Modawi, Khawla; Najmi, Alaa; Majrashi, Abdullah; Alhazmi, Luai; et al. (International Journal Of Community Medicine And Public Health, 2023)
Background: Numerous studies have assessed the prevalence of vitamin D insufficiency among Saudi individuals and correlated depression and anxiety with vitamin D deficiency. However, studies have not looked at these factors in Saudi Arabia's Jazan medical students. The current study aimed to clarify the relationship between low vitamin D levels, depression, anxiety, and academic performance. Methods: A cross-sectional study was conducted among medical students at Jazan university. The dependent variables were depression and anxiety, and their association with covariates, including sex, marital status, GPA, BMI, vitamin D level, and physical exercise, was evaluated. The 21-item depression, anxiety, and stress scale, which has been validated, was utilized. Results: Of 252 students, the prevalence of vitamin D deficiency was 54.4%; anxiety, 62.3%; and depression 68.7%. Comparatively, more female students than male students were vitamin D deficient. Stress was found to be substantially related to vitamin D deficiency (p<0.001). Anxiety was also significantly related to vitamin D deficiency (p<0.001), wherein the students with anxiety had a considerably higher prevalence of vitamin D deficiency than those without anxiety (84% vs. 32.5%). Similarly, depression was significantly associated with vitamin D deficiency (p<0.001), wherein students with depression were much more likely to get vitamin D deficiency than students without depression (86.7% vs. 27.5%)-no significant association otherwise with other variables. Conclusions: Stress, depression, and anxiety are associated with vitamin D deficiency. This finding highlights the importance of mental health promotion among medical students owing to its link to quality of life and academic performance.